Correlates of group sex participation among men who have sex with men in Chongqing, Southwestern China - Jin Chen; Hui Fan; Huailiang Chen; Feifei Yao (BMC, 2021)
Abstract Background Findings from specific countries indicated group sex was common among men who have sex with men (MSM), and men who reported group sex participation were at increased risk of human immunodeficiency virus (HIV)/sexually transmitted infections (STIs). The purpose of the current analysis was to describe the prevalence and correlates of group sex participation among a community-based sample of MSM in Chongqing, southwestern China. Methods Convenience sampling method was used to recruit participants and data were collected through an anonymous questionnaire. Logistic regression analysis was employed to identify correlates of group sex participation. Results Overall, 1151 eligible participants were enrolled in the study. 14.7% of MSM reported participating in group sex in their lifetime, and 5.8% reported group sex participation in the prior 6 months. Factors positively associated with group sex participation in both the prior 6 months and the lifetime included: monthly income ≥3000 Yuan (adjusted odds ratios [aOR] = 3.67, 95% confidence interval [CI] 1.25-10.75; aOR = 2.30, 95% CI 1.21-4.35), initiating anal sex before 18 years old (aOR = 1.86, 95% CI 1.03-3.34; aOR = 2.00, 95% CI 1.31-3.05), using gay apps to seek sex partners (aOR = 7.41, 95% CI 2.57-21.33; aOR = 9.75, 95% CI 4.92-19.33), recreational drug use (aOR = 10.10, 95% CI 5.52-18.49; aOR = 4.75, 95% CI 3.20-7.05) and having condomless internal ejaculation (CIE) (aOR = 3.66, 95% CI 2.01-6.68; aOR = 1.61, 95% CI 1.11-2.35). Factors only associated with group sex participation in the lifetime were older age (age between 26 and 35 years old: aOR = 2.06, 95% CI 1.30-3.26; age > 35 years old: aOR = 1.95, 95% CI 1.10-3.46) and history of STIs (aOR = 2.51, 95% CI 1.37-4.62). Conclusions The results of this study suggested that group sex participation was a potentially risky context for acquisition and transmission of HIV/STIs. Close attention should be given to MSM who participated in group sex, and appropriate risk reduction interventions should be developed specific to this subgroup of MSM.